Analyzing the path of Resource-based and Dynamic Capabilities Theories for explaining the differentiated performance of firms - De Montreuil Carmona, Linda Jessica (Revista de Negócios, 2023)
Analyzed both separately and jointly, Resource-Based Theory (RBT) and Dynamic Capabilities Theory (DCT) have been considered leading approaches focused on analyzing the performance of firms in dynamic market environments. Thus, the objective of this systematic literature review was to analyze the theoretical-epistemological trajectory of RBT and DCT in relation to performance and generation of competitive advantage, using six decades of scientific production, initially selecting a set of 939 articles and after filtering by thematic adherence and relevance, in a sample of 58 papers. The study of theories based on resources and capabilities becomes relevant due to the increase in the complexity of the corporate scenario, where new systems of production, innovation and technology, consumption, and exchange emerge every day, reaching the interests of the firm, its stakeholders, and markets. This article intends to serve as a guide for academics interested in both theories, as it is a theoretical body widely used in the Academy of Management, relevant due to its maturity in the area of Strategy.